2014
DOI: 10.4314/ejhs.v24i3.10
|View full text |Cite
|
Sign up to set email alerts
|

Oral health literacy among clients visiting a Rural Dental College in north India- A crosssectional study

Abstract: BackgroundLimited health literacy among adults is one of the many barriers to better oral health outcomes. It is not uncommon to find people who consider understanding oral health information a challenge. Therefore, the present study assessed oral health literacy among clients visiting Gian Sagar Dental College and Hospital, Rajpura.Materials and MethodsA cross-sectional study was conducted on 450participants who visited the Out Patient Department (OPD) of Gian Sagar Dental College and Hospital for a period of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
3
11
1
Order By: Relevance
“…Conceptual knowledge scores of male participants in the present study were lower compared to the female participants; a similar trend has been reported in the findings of study conducted by Gambhir et al . [ 14 ] Higher income and better education were associated with higher levels of CMOHK scores similar to the findings of the study conducted by McQuistan et al . [ 12 ]…”
Section: Discussionsupporting
confidence: 88%
“…Conceptual knowledge scores of male participants in the present study were lower compared to the female participants; a similar trend has been reported in the findings of study conducted by Gambhir et al . [ 14 ] Higher income and better education were associated with higher levels of CMOHK scores similar to the findings of the study conducted by McQuistan et al . [ 12 ]…”
Section: Discussionsupporting
confidence: 88%
“…[Binkley, Matheson and Williams, 1997] LMICs like Bangladesh, Mozambique, India, Zambia and sub-Saharan countries also researched the association of health literacy with oral health, child nutritional status, cardiovascular mortality and HIV infection. [McClintock, et al, 2017;Tique et al, 2017;Johri et al , 2016;Ramandeep, et al, 2014;Schrauben and Wiebe, 2017;Das, et al, 2017].…”
Section: Discussionmentioning
confidence: 99%
“…The results of Naghibi Sistani et al (23) are in line with the findings of the present study. In another study in India, Ramandeep et al (24) distributed a researcher-made questionnaire among the subjects referred to the dental school, and the degree of favorable oral health literacy was obtained as 12.5%. In the present study, the mean oral health literacy was 11.09 ± 3.18 in females and 10.15 ± 3.65 in males and there was a positive correlation between health literacy and female gender (linear regression coefficient = 0.91 and P value = 0.01, Table 3).…”
Section: Discussionmentioning
confidence: 99%